Design of Cryptographic Hardware Module Using FPGA - Muhammad Imran, Ahmad; Abdul Rahman, Mohd Saad; Mohd Nazrin, Md Isa; Mohd Taufik, Jusoh; Amir Razif Arief, Jamil Abdullah (Universiti Teknologi MARA (UiTM), 2009)
Organized by MARA University of Technology, Penang Campus, 8th - 9th December 2006 at UiTM Penang.